Gagasan Pengembangan Metode Konseling Islami dalam Perspektif Integratif - Hajir Tajiri (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2015)
Methodologically, the development of Islamic social sciences including Islamic counseling is not adhered to the closed system. The development of social sciences of Islam despite its underlying principles have proliferated since the heyday of Islam, but after it stagnated until a long time, and then science appeared and evolved spectacularly in the Western world. The position of Islamic science must show his position on the development of Western science, selecting and sorting, adapting back and perform filtering on a region where science is consistent or inconsistent with the principles of Islam. Some scientific theories developed in the West recognized store a number of shortcomings, but as a product of science the theory is not entirely rejected, and even quite useful in explaining the phenomenon of human behavior. Islamic counseling with integrative approach is allowing for the development of new methods of Islamic counseling.